Pengembangan Wilayah Kerja Pembangunan (WKP) II Provinsi Banten Berdasarkan Identifikasi Lokasi Potensial - Arlan Marzan; Isvan Taufik; Rahmat Hidayat; Regen; Resti Meliana Sari (Universitas Muhammadiyah Palembang, 2024)
To accelerate regional development in Banten Province, especially in the Development Work Area (WKP) II, which includes Serang City, Cilegon City, and Serang Regency, one of the efforts that needs to be made is to accelerate development in the Provincial Strategic Area (KSP). However, this will affect how much space is needed for activities, so it is necessary to control the area. One way to do this is through the arrangement of buildings and the environment. In determining the area to be developed, studies are needed to obtain potential locations so that they can be directed to buildings and environments that are expected to control the development of the area as well as maintain sustainable development. The purpose of this study is to identify potential locations and provide direction for building and environmental arrangements in potential locations at the KSP in WKP II. Data collection methods include desk study and survey methods, data processing with overlay analysis methods, and qualitative descriptive analysis. This research resulted in potential locations to be developed in KSP at WKP II, which include Serang City Veteran Road Corridor, Anyer Urban Area, the area around Situ Rawa Arum Cilegon City, Old Banten Site Area, KP3B Surrounding Area, Cikeusal Toll Opening Corridor, and Kopo Residential Area.